#TITLE_ALTERNATIVE# - BONIFASIO NUGRAHA PERDANA HARDJOSOEKANTA (NIM: 13204104), LUCAS
In this final project, thirteen pairs of Chest X-ray images from RS H.A. Rotinsulu are used. Program is built by using Matlab. After running the program, the mean of MI value after registration using rigid transformation increase 7.937% compare with mean of MI value before registration. For registration using affine transformation, the increasing value is 10.692%. Standard deviation value for registration using rigid transformation is decrease 5,375%, and using affine transformation decrease 8.042%, compare with standard deviation value before registration.